Ionic Solids

A new ionic solid with voids in the crystal lattice enhances functional properties, enabling applications in electrochemical devices and molecular recognition by incorporating specific substances, addressing the limitations of traditional ionic solids.

JP7599174B2Active Publication Date: 2024-12-13THE JAPAN SCI & TECH AGENCY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021516272
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-25
Filing Date
2020-04-24
Publication Date
2024-12-13
Estimated Expiration
2040-04-24

AI Technical Summary

Technical Problem

Existing ionic solids lack new functional properties and are limited in applications beyond traditional Coulombic interactions, making them less versatile for advanced technologies.

Method used

Development of a new type of ionic solid with voids in the crystal lattice that can incorporate substances, allowing for enhanced functionalities such as electrochemical device materials, gas adsorption materials, and molecular recognition materials by incorporating substances like water, polyacids, inorganic salts, and hydrophilic substances with specific molecular weights.

Benefits of technology

The new ionic solid exhibits improved properties for various applications, including high ionic conductivity, gas adsorption, solvent vapor adsorption, and molecular recognition, making it suitable for electrochemical devices and reaction field provision.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599174000006
    Figure 0007599174000006
  • Figure 0007599174000007
    Figure 0007599174000007
  • Figure 0007599174000008
    Figure 0007599174000008
Patent Text Reader

Abstract

An ionic solid having void spaces in which a substance is to be incorporated.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ionic solids.

[0002] For example, sodium chloride is known as an ionic solid that exists in nature, and this ionic solid has a structure in which positive ions and negative ions are attracted to each other by Coulomb force (electrostatic force) and are arranged alternately and tightly bonded. The present inventors have been studying the structure of salts of ionic polynuclear metal complexes from the standpoint of supramolecular chemistry, and have reported on a new type of ionic solid that differs from ionic solids that exist in nature and in which non-Coulombic interactions govern the spatial arrangement. Non-Patent Documents 1 and 2 report a polynuclear metal complex with penicillamine as a ligand [Co2Au3(D-pen-N,S)6 3- It has been reported that when producing salt crystals, even slight differences in pH during production can significantly affect the porosity, which is an indicator of porosity, and that water vapor, carbon dioxide, etc. are adsorbed into the pores. The present inventors have also filed patent applications regarding non-Coulomb force dominated ionic solids (Patent Documents 1 and 2). Patent Document 1 describes a charge-separated ionic solid characterized in that a single crystal of a salt of a cationic polynuclear metal complex forms cationic clusters, and the cationic clusters are arranged in a close-packed structure to form vacancies in which clusters of counter anions are accumulated. This ionic solid differs from ionic solids found in nature in that the ions are not paired, but the ionic clusters have a crystal structure in which charges are separated by non-Coulomb forces. Due to this unique structure, the solid exhibits dielectric properties and a negative electrostrictive effect. Patent Document 2 describes an ionic solid in which single crystals of a salt of an anionic polynuclear metal complex are accumulated to form a crystal lattice, and cationic species are present in the gaps of the crystal lattice. In this ionic solid, the metal cations have high fluidity inside the ionic solid, and the solid is said to function as an ion exchanger that replaces external metal cations, and the fluidity of the cationic ions is unlikely to decrease even when pellets are formed. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 56237 [Patent Document 2] WO 2018 / 79831 [Non-patent literature]

[0004] [Non-Patent Document 1] Chem. Asian J. 2016, 11, 486-490 [Non-Patent Document 2] Chem. Commun., 2016, 52, 12893-12896 Summary of the Invention [Problem to be solved by the invention]

[0005] Another object of the present invention is to provide an ionic solid having a new function. [Means for solving the problem]

[0006] The present inventors have conducted various studies to impart new functions to the ionic solid described in Non-Patent Document 2, and have succeeded in developing a novel ionic solid in which a specific substance is incorporated into the voids in the crystal lattice of the ionic solid described in Non-Patent Document 2. The present inventors have then found that such an ionic solid is useful as an electrochemical device material, a reaction field providing material, a gas adsorption material, a solvent vapor adsorption material, a molecular recognition material, a metal ion exchanger, an anion exchanger, or the like.

[0007] The present invention provides the following [1] to

[32] . [1] An ionic solid that has voids for trapping substances. [2] The ionic solid according to [1] above, wherein the voids are formed by a crystal lattice of a metal complex. [3] The ionic solid according to [1] or [2] above, which contains in its voids one or more substances selected from the group consisting of water, polyacids, inorganic salts, metal ions, oxoanions, and hydrophilic substances having a molecular weight of 60 or more. [4] The ionic solid according to [3] above, wherein the hydrophilic substance is one or more selected from the group consisting of polyhydric alcohols having a molecular weight of 60 or more, cyclic oligosaccharides having a molecular weight of 60 or more, saccharides having a molecular weight of 60 or more, sugar alcohols having a molecular weight of 60 or more, and amino acids having a molecular weight of 60 or more. [5] The ionic solid according to any one of the above [1] to [4], wherein the voids occupy 40% or more of the crystal lattice. [6] The ionic solid according to any one of the above [1] to [5], wherein the opening diameter of the voids is 0.5 to 5 nm. [7] The ionic solid according to any one of the above [1] to [6], which is an electrochemical device material, a reaction field providing material, a gas adsorption material, a solvent vapor adsorption material, a molecular recognition material, a metal ion exchanger, or an anion exchanger. [8] A column packing material using the ionic solid according to any one of [1] to [7] above. [9] A catalyst carrier using the ionic solid according to any one of [1] to [7] above.

[0008]

[10] The ionic solid according to any one of the above [2] to [9], wherein the metal complex is an anionic metal complex (A) and a cationic species (B) arranged via a coordinate bond or an ionic bond.

[0009]

[11] (A) An anionic metal complex is a metal complex having two metals M which may be the same or different and are selected from the elements of Group 9 of the periodic table. 1 and three metals M, which may be the same or different, selected from the elements of Group 11 of the periodic table. 2 and M bound via one ligand 1 M 2 The ionic solid according to

[10] above, which is a pentanuclear complex anion.

[12] The ionic solid according to

[11] above, wherein the ligand is an amino acid having a thiol group.

[13] The ionic solid according to any one of the above

[10] to

[12] , wherein the anionic metal complex (A) is a metal complex represented by the following general formula (1):

[0010] [(M 1 ) d (M 2 ) e (X 1 ) f ] k- (1)

[0011] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, X 1 represents an amino acid having a thiol group, d is a number from 0 to 4, e is a number from 0 to 4, f is a number from 1 to 8, k represents a number from 1 to 4. However, d and e cannot be 0 at the same time.)

[0012]

[14] The ionic solid according to any one of the above

[10] to

[13] , wherein the cationic species (B) is a metal complex represented by the following general formula (2):

[0013] A a [(M 3 ) l (X 2 ) m ] j (2)

[0014] (In the formula, A represents an alkali metal ion or an alkaline earth metal ion; M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate, a represents a number from 0 to 10, l is a number between 0 and 1, m is a number from 1 to 6, j represents a number from 1 to 3. However, a and l cannot be 0 at the same time.)

[0015]

[15] The ionic solid according to any one of the above

[10] to

[14] , wherein the (B) cationic species includes a cationic metal complex.

[16] The ionic solid according to

[15] above, wherein the cationic metal complex is one or more selected from the following compound group α:

[0016] <Compound group α> [Co(NH3)6] 3+ , [Co(H2O)(NH3)5] 3+ , [Co(NO2)(NH3)5] 2+ , [Co(H2O)6] 2+ , [Ni(H2O)6] 2+ , [Mn(HO)] 2+ , [Co(H2O)4] 2+ , [Ni(H2O)4] 2+ , [Mn(H2O)4] 2+, {Li[Zn(OAc)2]} + , {Na[Zn(OAc)2]} + , {K[Zn(OAc)2]} + , {Cs[Zn(OAc)2]} + , {Na2Cs7[Zn(OAc)2]} 9+ , {Na9[Zn(OAc)2]} 9+ , [Co(en)3] 3+ , [Co(tn)3] 3+ (where OAc stands for acetate ion, en stands for ethylenediamine, and tn stands for 1,3-diaminopropane.)

[0017]

[17] The ionic solid according to any one of [2] to

[16] above, wherein the crystal lattice contains a metal complex represented by the following general formula (3):

[0018] [(M 1 )3(M 2 )2(X 1 )6]2[(M 3 )(X 2 ) m1 ]3·nH2O (3)

[0019] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, or a carboxylate, m1 is a number from 1 to 6, n is a number from 1 to 100.

[0020]

[18] The ionic solid according to any one of the above [2] to

[16] , wherein the crystal lattice contains a metal complex represented by the following general formula (4):

[0021] (A) a [(M 1 )3(M 2 )2(X 1 )6] b [(M 3 ) l (X 2 ) m2 ] c nH2O (4)

[0022] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate; A's each independently represent an alkali metal ion or an alkaline earth metal ion; a represents a number from 0 to 10, b is a number from 1 to 3, c is a number from 1 to 3, l is a number between 0 and 1, m2 is a number from 1 to 6, n represents a number from 1 to 100. However, a and l cannot be 0 at the same time.)

[0023]

[19] The ionic solid according to any one of the above [2] to

[16] , wherein the crystal lattice contains a metal complex represented by the following general formula (5):

[0024] (A)9[(M 1 )3(M 2 )2(X 1 )6]3[(M 3 )(X 2 ) m3 ]2·nH2O (5)

[0025] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, or a carboxylate, A's each independently represent an alkali metal ion or an alkaline earth metal ion; m3 represents the numbers 1 to 6, n is a number from 1 to 100.

[0026]

[20] The ionic solid according to any one of [2] to

[19] above, which exhibits bulk ionic conductivity.

[0027]

[21] The ionic solid according to any one of the above [2] to [9], wherein the metal complex is a cationic polynuclear metal complex in which polynuclear metal complexes each composed of a metal ion, a metal element, and a ligand are accumulated.

[22] The ionic solid according to

[21] above, wherein the cationic polynuclear metal complex is a 9- to 200-nuclear cationic metal complex.

[23] The ionic solid according to

[21] or

[22] above, wherein the cationic polynuclear metal complex is an accumulation of one or more polynuclear metal complexes each comprising an ion of a metal A selected from Group 11 of the periodic table, one or more transition metals B other than the metal A, and one or more ligands selected from a tripodal phosphine and an amino acid having a thiol group.

[24] The ionic solid according to any one of the above

[21] to

[23] , wherein the cationic polynuclear metal complex comprises a polynuclear metal complex represented by the following formula (11):

[0028] [M 11 6M 12 h (X 11 ) ma (X 12 ) 3ma ] na (11)

[0029] (In the formula, M 11 represent, independently of each other, an ion of a metal A selected from Group 11 of the Periodic Table, M 12 each independently represents a transition metal B other than metal A, X 11 represent, independently of one another, a tripodal phosphine, X 12 each independently represents an amino acid having a thiol group, h represents 3 or 6; ma represents 1 or 2; and na represents an integer from 1 to 18.

[0030]

[25] The ionic solid according to any one of the above

[21] to

[24] , wherein the crystal lattice is formed by a compound represented by the following formula (12):

[0031] [{M 11 6M 12 h (X 11 ) ma (X 12 ) 3ma} na (M 12p M 13 q )](E) r (12)

[0032] (In the formula, M 11 represent, independently of each other, an ion of a metal A selected from Group 11 of the Periodic Table, M 12 each independently represents a transition metal B other than metal A, M 13 each independently represents a metal other than metal A, X 11 represent, independently of one another, a tripodal phosphine, X 12 each independently represents an amino acid having a thiol group, h represents 3 or 6; ma represents 1 or 2; na represents an integer from 1 to 18; E represents an anion or an inorganic acid; p, q, and r each independently represent an integer of 0 or 1 or more, provided that p, q, and r cannot simultaneously be 0.

[0033]

[26] The ionic solid according to any one of the above

[21] to

[25] , wherein the transition metal B is one or more selected from the group consisting of Pd, Ni, Zn, Pt, Cd, Cu and Mn.

[27] The ionic solid according to any one of the above

[21] to

[26] , which contains a tripodal phosphine and an amino acid having a thiol group as ligands, and the ratio of the tripodal phosphine to the amino acid having a thiol group (tripodal phosphine / amino acid having a thiol group) is 1 / 3 to 1 / 2.

[28] The ionic solid according to any one of the above

[21] to

[27] , wherein the tripodal phosphine is 1,1,1-tris(diphenylphosphinomethyl)ethane and the amino acid having a thiol group is penicillamine.

[29] The ionic solid according to any one of the above

[21] to

[28] , wherein voids are used as reaction fields.

[30] The ionic solid according to any one of the above

[21] to

[29] , wherein the voids are used as a reaction field for a condensation reaction.

[31] The ionic solid according to any one of the above

[21] to

[30] , wherein the voids are used as a reaction field for a condensation reaction of an oxoanion.

[0034]

[32] A method for producing an oxide, comprising using the voids in the ionic solid according to any one of

[21] to

[31] as a reaction field for an oxidation reaction. Effect of the Invention

[0035] According to the present invention, a novel ionic solid can be provided. The ionic solid of the present invention exhibits various properties by incorporating a substance into the voids, and is therefore useful, for example, as an electrochemical device material, a reaction field providing material, a gas adsorption material, a solvent vapor adsorption material, a molecular recognition material, a metal ion exchanger, an anion exchanger, etc. [Brief description of the drawings]

[0036] [Figure 1] FIG. 2 shows synthesis schemes for the ionic solids obtained in Synthesis Examples 2 and 3. [Diagram 2] FIG. 2 is a diagram showing the crystal structure of the ionic solid obtained in Synthesis Example 2. [Diagram 3] FIG. 2 is a diagram showing the crystal structure of the ionic solid obtained in Synthesis Example 3. [Figure 4] FIG. 2 shows Raman spectra of the ionic solids obtained in Synthesis Examples 2 and 3, and Examples 16, 19, and 20. [Diagram 5] FIG. 1 shows 1H-NMR spectra of the ionic solids obtained in Examples 10, 16, 19, and 20. [Figure 6] FIG. 2 shows the crystal structure of the ionic solid obtained in Example 24. [Figure 7] FIG. 2 shows the crystal structure of the ionic solid obtained in Example 26. [Figure 8] FIG. 1 shows the performance of the ionic solid obtained in Example 10 and Synthesis Example 2 as a gas adsorption material. [Figure 9] FIG. 2 shows the performance of the ionic solid obtained in Example 25 as a solvent vapor adsorption material. [Figure 10] FIG. 2 shows IR spectra of the ionic solids obtained in Examples 31 to 33. [Figure 11] FIG. 3 shows an ESI-mass spectrum of the ionic solid obtained in Example 34. [Figure 12] FIG. 3 shows the IR spectrum of the ionic solid obtained in Example 34. [Figure 13] FIG. 35 shows the performance of the ionic solid obtained in Example 35 as a reaction field-providing material. [Figure 14] FIG. 35 shows the performance of the ionic solid obtained in Example 35 as a reaction field-providing material. [Figure 15] FIG. 35 shows the performance of the ionic solid obtained in Example 35 as a reaction field-providing material. [Figure 16] FIG. 35 shows the performance of the ionic solid obtained in Example 35 as a reaction field-providing material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] The "ionic solid" according to the present invention is not particularly limited as long as it is an ionic solid having voids for incorporating substances. Preferred embodiments include, for example, a crystal lattice forming the voids is formed from cationic species and anionic species, and a crystal lattice formed from ionic crystals.

[0038] [First embodiment] The ionic solid according to this embodiment is characterized by having voids for taking in substances. Here, in this specification, the term "ionic solid" refers to a non-Coulomb-dominated ionic solid in which cations and anions are sparsely arranged, rather than a Coulomb-dominated ionic solid in which cations and anions are densely arranged, and the ionic solid as a whole is kept neutral.

[0039] In ionic solids, a crystal lattice is formed by a three-dimensional framework structure in which cationic or anionic molecules are linked together, and the crystal lattice has voids (spaces). The porosity of the crystal lattice is usually 40% or more, preferably 60% or more in the crystal lattice. Here, the "porosity" in this specification is a value obtained by the method described in J. Appl. Cryst., 41, 466-470, 2008. That is, it can be calculated by using "volume of single crystal x porosity in unit cell" based on the solvent accessible void (void volume in unit cell) calculated by the VOID function of crystal structure display software (Mercury; J. Appl. Cryst. (2008). 41, 466-470). The opening diameter of the voids is usually 0.5 nm or more, preferably 0.5 to 5 nm, more preferably 0.8 to 5 nm, and even more preferably 1.5 to 4 nm. In this specification, the "opening diameter" can be measured by X-ray diffraction.

[0040] The crystal lattice is not particularly limited as long as cationic or anionic molecules are linked to form a three-dimensional framework structure, but is preferably formed by a metal complex, and is preferably an ionic solid in which (A) an anionic metal complex and (B) a cationic species are arranged by coordinate bonds or ionic bonds, or a metal complex including a cationic polynuclear metal complex composed of a metal ion, a metal element, and a ligand is accumulated.

[0041] The voids of the ionic solid can incorporate one or more substances. The incorporation of a substance can be achieved, for example, by immersing the ionic solid in a solution containing the substance and allowing the substance to be incorporated into the voids through the openings of the ionic solid. Here, in this specification, "incorporating a substance" refers to including a substance in the voids of the ionic solid, and is a concept that includes supporting, including, and adsorbing.

[0042] The encapsulated substance is not particularly limited, and examples thereof include gas, liquid, and solid. Among them, liquid and solid are preferable in terms of easily enjoying the effects of the present invention, and one or more selected from water, inorganic salts, metal ions, oxoanions, and hydrophilic substances having a molecular weight of 60 or more are more preferable. When the voids are filled with water, the large dielectric constant of water can reduce the Coulomb attraction. Whether the voids of the crystal lattice are filled with water can be determined by a combination of X-ray structural analysis (presence of oxygen atoms), CHN elemental analysis (presence of water), IR spectrum (presence of OH stretching derived from water), and TG-DTA analysis (weight loss at 100°C or less). In addition, when inorganic salts, metal ions, or hydrophilic substances are encapsulated in the voids, excellent ion conductivity can be exhibited. Furthermore, the voids can be used as a reaction field for chemical reactions. These functions will be described later.

[0043] The metal ion is preferably a monovalent or divalent metal cation, such as a sodium ion, a potassium ion, a copper ion, or a cadmium ion. The inorganic salt is not particularly limited as long as it is soluble in water and aprotic polar solvents, and examples thereof include nitrates such as cadmium nitrate and copper nitrate.

[0044] Examples of hydrophilic substances having a molecular weight of 60 or more include organic compounds having a molecular weight of 60 or more and having a hydroxyl group, a sulfanyl group, an amino group, a carboxyl group, or an amide group. Specific examples include one or more selected from polyhydric alcohols having a molecular weight of 60 or more, cyclic oligosaccharides having a molecular weight of 60 or more, saccharides having a molecular weight of 60 or more, sugar alcohols having a molecular weight of 60 or more, and amino acids or derivatives thereof having a molecular weight of 60 or more.

[0045] Examples of polyhydric alcohols having a molecular weight of 60 or more include ethylene glycol and polyethylene glycol. Examples of cyclic oligosaccharides having a molecular weight of 60 or more include α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin. Examples of saccharides having a molecular weight of 60 or more include monosaccharides such as glucose, and disaccharides such as sucrose, lactose, maltose, and trehalose. Examples of sugar alcohols having a molecular weight of 60 or more include maltitol, arabitol, xylitol, sorbitol, adonitol, galactitol, and erythritol. Examples of amino acids or derivatives thereof having a molecular weight of 60 or more include penicillamine and aspartic acid.

[0046] The ionic solid according to this embodiment can be used as, for example, an electrochemical device material such as an ion secondary battery, an electrochromic element, or a thermoelectric element, a reaction field providing material for oxidation reactions, etc., as well as a gas adsorption material, a solvent vapor adsorption material, a molecular recognition material, a metal ion exchanger, an anion exchanger, etc. These applications will be described later.

[0047] Second Embodiment The ionic solid according to this embodiment is an ionic solid having voids for taking in substances, the voids being formed by a crystal lattice of a metal complex, and the metal complex is formed by arranging (A) anionic metal complex and (B) cationic species by coordinate bonds or ionic bonds. The ionic solid according to this embodiment has (A) anionic metal complex and (B) cationic species, but formally, (A) anionic metal complex and (B) cationic species associate as salts, so that the ionic solid as a whole maintains neutrality and can be isolated as crystals. In addition, the voids in the crystal lattice formed by arranging (A) anionic metal complex and (B) cationic species may be filled with water. In this specification, the term "anionic metal complex" refers to a metal complex that dissociates with a counter cation and behaves as an anion when dissolved in a polar solvent such as water or alcohol. The term "cation species" refers to inorganic ions such as aqua cations of metals. The porosity and opening size of the ionic solid according to this embodiment are as described above.

[0048] The anionic metal complex (A) is a metal complex anion consisting of a metal element and a ligand. From the viewpoint of porosity and ionic conductivity, a metal complex anion consisting of two kinds of metal elements and one kind of ligand is preferred, and a polynuclear complex anion consisting of a metal element selected from Groups 6, 9 and 13 of the periodic table and a metal element selected from Groups 10 and 11 of the periodic table bonded via one kind of ligand is more preferred. The polynuclear metal anion is preferably a polynuclear complex anion consisting of two metal elements (M 1 ) and three metal elements (M 2 ) bound via one ligand, M 1 M 2 Pentanuclear complex anions are more preferred.

[0049] Examples of metal elements in Groups 6, 9, and 13 of the periodic table include Co, Rh, Ir, Cr, Mo, W, B, Al, Ga, In, and Tl. Among these, from the viewpoints of porosity and ion conductivity, metal elements in Group 9 of the periodic table are preferred, Co and Rh are more preferred, and Co is even more preferred. Examples of metal elements in Groups 10 and 11 of the periodic table include Au, Ag, Cu, Pt, Pd, and Ni. Among these, from the viewpoints of porosity and ion conductivity, metal elements in Group 11 of the periodic table are preferred, Au and Ag are more preferred, and Au is even more preferred.

[0050] Known ligands can be used as the ligand, but a multidentate ligand having multiple coordination sites for a metal ion is preferred because it can form a coordinate bond with the metal ion in a stable chelate structure. In particular, it is preferred to have a thiol group that can stably form a metal-ligand bond in water, and an amino acid having a thiol group is more preferred. There is no particular limitation on the relative positions of the amino group and the carboxyl group, and it is not limited to α-amino acids, and the carboxyl group may be at the so-called ω position. In addition, it is preferred that the amino group and the thiol group are arranged to form a chelate structure with respect to the metal, and it is more preferred that they are arranged at the β or γ position of the carboxyl group. Examples of such compounds include cysteine, penicillamine (D-pen), N-methylcysteine, N-methylpenicillamine, N,N'-ethylenebiscysteine, and N,N'-ethylenebispenicillamine (D-epen). The ligand can have one or more types.

[0051] A suitable example of the anionic metal complex (A) used in the ionic solid of this embodiment is one represented by the following general formula (1).

[0052] [(M 1 ) d (M 2 ) e (X 1 ) f ] k- (1)

[0053] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, X 1 represents an amino acid having a thiol group, d is a number from 0 to 4, e is a number from 0 to 4, f is a number from 1 to 8, k represents a number from 1 to 4. However, d and e cannot be 0 at the same time.)

[0054] In addition, M 1 , M 2 Metal elements according to X 1 The amino acid having a thiol group according to the formula (I) is as described above. 1 When there are multiple, they may be the same or different, and M 2 and X 1 The same is true for.

[0055] The (B) cationic species preferably contains a cationic metal complex from the viewpoint of porosity and ion conductivity. The cationic metal complex is composed of a metal element and a ligand, and from the viewpoint of porosity and ion conductivity, a cationic metal complex having one kind of metal element as a center and a ligand bonded thereto is preferable, a cationic metal complex having a metal element selected from Groups 7, 9, 10, and 12 of the periodic table as a center and a ligand bonded thereto is more preferable, and a cationic metal complex having a metal element selected from Groups 9 and 12 of the periodic table as a center and a ligand bonded thereto is even more preferable.

[0056] Examples of metal elements in Groups 7, 9, 10 and 12 of the periodic table include Mn, Tc, W, Co, Rh, Ir, Ni, Pd, Pt and Zn. Among these, from the viewpoints of porosity and ion conductivity, metal elements in Groups 9 and 12 of the periodic table are preferred, and Co or Zn is more preferred.

[0057] The ligand is not particularly limited as long as it can form a stable cationic metal complex by coordinating with the metal element, and known ligands can be used, and one or more types can be included. For example, water, ammine, diamine, inorganic acid ion, carboxylate, dicarboxylate, etc. can be mentioned. For example, diamine can be ethylenediamine, 1,3-diaminopropane, etc., and for example, inorganic ion can be halide ion, nitrite ion, nitrate ion, sulfate ion, borate ion, phosphate ion, cyanate ion, thiocyanate ion, silicate ion, etc. can be mentioned. For example, carboxylate can be formate ion, acetate ion, trifluoroacetate ion, propionate ion, benzoate ion, etc., and for example, dicarboxylate can be fumarate ion, benzenedicarboxylate ion, etc. can be mentioned. Among them, from the viewpoint of porosity and ion conductivity, water, ammine, diamine, inorganic ion, and carboxylate are preferable, and water, ammine, acetate ion, ethylenediamine, and 1,3-diaminopropane are more preferable.

[0058] The (B) cation species used in the ionic solid of the present embodiment may contain an alkali metal ion or an alkaline earth metal ion as long as it contains a cationic metal complex, and examples of such cationic species include metal complexes represented by the following general formula (2).

[0059] A a [(M 3 ) l (X 2 ) m ] j (2)

[0060] (In the formula, A represents an alkali metal ion or an alkaline earth metal ion; M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate, a represents a number from 0 to 10, l is a number between 0 and 1, m is a number from 1 to 6, j represents a number from 1 to 3. However, a and l cannot be 0 at the same time.)

[0061] Examples of alkali metal ions include Li + , Na + , K + , Cs + , Rb + Examples of alkaline earth metal ions include Mg 2+ , Ca 2+ etc. can be mentioned. In addition, M 3 Specific examples of metal elements of Groups 9 and 12 of the periodic table are as described above. 3 When there are multiple X's, they may be the same or different. 2 The same is true for.

[0062] Specific examples of suitable cationic metal complexes include those shown in the following compound group α, and the compound may have one or more kinds.

[0063] <Compound group α> [Co(NH3)6] 3+ , [Co(H2O)(NH3)5] 3+ , [Co(NO2)(NH3)5] 2+ , [Co(H2O)6] 2+ , [Ni(H2O)6] 2+ , [Mn(HO)] 2+ , [Co(H2O)4] 2+ , [Ni(H2O)4] 2+ , [Mn(H2O)4] 2+ , {Li[Zn(OAc)2]} + , {Na[Zn(OAc)2]} + , {K[Zn(OAc)2]} + , {Cs[Zn(OAc)2]} + , {Na2Cs7[Zn(OAc)2]} 9+ , {Na9[Zn(OAc)2]}9+ , [Co(en)3] 3+ , [Co(tn)3] 3+ (where OAc stands for acetate ion, en stands for ethylenediamine, and tn stands for 1,3-diaminopropane.)

[0064] The crystal lattice of the ionic solid of this embodiment preferably contains a metal complex represented by the following formula (3), (4) or (5). One or more of such metal complexes may be contained.

[0065] [(M 1 )3(M 2 )2(X 1 )6]2[(M 3 )(X 2 ) m1 ]3·nH2O (3)

[0066] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, or a carboxylate, m1 is a number from 1 to 6, n is a number from 1 to 100.

[0067] (A) a [(M 1 )3(M 2 )2(X 1 )6] b [(M 3 ) l (X 2 ) m2 ] c nH2O (4)

[0068] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate; A's each independently represent an alkali metal ion or an alkaline earth metal ion; a represents a number from 0 to 10, b is a number from 1 to 3, c is a number from 1 to 3, l represents a number between 0 and 1 m2 is a number from 1 to 6, n represents a number from 1 to 100. However, a and l cannot be 0 at the same time.)

[0069] (A)9[(M 1 )3(M 2 )2(X 1 )6]3[(M 3 )(X 2 ) m3 ]2·nH2O (5)

[0070] (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table, M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate, A's each independently represent an alkali metal ion or an alkaline earth metal ion; m3 represents the numbers 1 to 6, n is a number from 1 to 100.

[0071] In the above formulas (3) to (5), m1, m2, and m3 are preferably numbers from 2 to 6, and n is preferably a number from 2 to 50. 1 , M 2 , M 3 Metal elements according to X 1 The amino acid having a thiol group according to the formula (I) and the alkali metal ion and alkaline earth metal ion according to the formula (A) are as described above. 1 When there are multiple, they may be the same or different, and M 2 , M 3 , X 1 , the same is true for A.

[0072] An example of an ionic solid formed in a crystal lattice containing a metal complex represented by the above general formula (4) or (5) is shown in Figures 2 and 3. As shown in Figures 2 and 3, the opening diameter of the voids in the crystal lattice is 0.5 nm or more, and the porosity of the crystal lattice is 40% or more.

[0073] In addition, various substances such as water can be incorporated into the gaps in the crystal lattice formed by the arrangement of (A) anionic metal complexes and (B) cationic species. In particular, it was found that while hydrophilic substances with small molecular weights cannot be encapsulated, those with a molecular weight of 60 or more can be specifically encapsulated. Further detailed investigations revealed that ionic solids encapsulating such hydrophilic substances exhibit excellent ionic conductivity. In view of the relationship with the voids, the molecular weight of the hydrophilic substance is preferably at least 70, more preferably at least 80. The upper limit of the molecular weight of the hydrophilic substance is preferably 1600, more preferably 1500, in view of ease of inclusion.

[0074] Examples of hydrophilic substances having a molecular weight of 60 or more include organic compounds having a molecular weight of 60 or more and a hydroxyl group, a sulfanyl group, an amino group, a carboxyl group, or an amide group, and specific examples thereof are the same as those described above. Among them, from the viewpoint of ion conductivity, polyhydric alcohols having a molecular weight of 60 or more, cyclic oligosaccharides having a molecular weight of 60 or more, saccharides having a molecular weight of 60 or more, sugar alcohols having a molecular weight of 60 or more, and amino acids having a molecular weight of 60 or more are preferred. Note that one or more types of hydrophilic substances can be used.

[0075] The incorporation of the hydrophilic substance can be achieved, for example, by immersing the ionic solid in a hydrophilic substance, water containing the hydrophilic substance, or an aqueous organic solvent solution containing the hydrophilic substance, and allowing the hydrophilic substance to be incorporated into the voids through the openings in the ionic solid. The organic solvent is not particularly limited as long as it is water-soluble, and for example, an alcohol such as ethanol can be used. Furthermore, in an ionic solid incorporating a hydrophilic substance, a compound different from the hydrophilic substance may be included in the voids of the crystal lattice and / or in the hydrophilic substance.

[0076] The ionic solid according to this embodiment can be produced by an appropriate method, for example, by reacting a salt of an anionic metal complex with a cationic metal complex. The salt of an anionic metal complex and the cationic metal complex may be produced by a known method. The reaction between metal complexes may be carried out, for example, by stirring the salt of an anionic metal complex and the cationic metal complex in a solvent such as water or acetic acid / potassium acetate buffer. The isolation operation may be carried out, for example, by washing with an alcohol such as ethanol and then separating by filtration or the like.

[0077] The ionic solid according to this embodiment can be applied to various applications described in the first embodiment by incorporating various substances into the voids. For example, by including a hydrophilic substance in the voids of the crystal lattice, the ionic conductivity is high and bulk ionic conductivity can be exhibited. In addition, xylitol, arabitol, and adonitol are sugars with the same molecular weight, and as shown in the examples below, xylitol is more easily included than arabitol and adonitol, so it can be used as a molecular recognition material. Furthermore, the ionic solid represented by the above formula (2) can further enhance ionic conductivity by including metal ions in the voids of the crystal lattice, so that the metal ions can move in the ionic solid, and it is useful as an electrochemical device material such as an ion secondary battery, an electrochromic element, and a thermoelectric element.

[0078] Third Embodiment The ionic solid according to the present embodiment is an ionic solid having voids for taking in substances, the voids being formed by a cationic polynuclear metal complex, i.e., a crystal lattice of a metal complex, and the crystal lattice of the cationic polynuclear metal complex is characterized in that one or more polynuclear metal complexes consisting of a metal ion, a metal element, and a ligand are accumulated. In the ionic solid according to the present embodiment, the cationic polynuclear metal complex and an anion are ionic bonded to each other, and the ionic solid as a whole is kept neutral. Here, in this specification, the term "cationic metal complex" refers to a metal complex that ionizes with a counter anion and behaves as a cation when dissolved in a polar solvent such as water or alcohol. The porosity and opening size of the ionic solid according to the present embodiment are as described above.

[0079] The cationic polynuclear metal complex is an accumulation of polynuclear metal complexes, and preferably has 9 to 200 nuclei, more preferably 13 to 160 nuclei.

[0080] Examples of metal ions constituting the cationic polynuclear metal complex include ions of metals selected from Group 9 of the periodic table, ions of metals selected from Group 11 of the periodic table, and ions of metals selected from Group 12 of the periodic table. Among these, ions of metal A selected from Group 11 of the periodic table are preferred, and one or more metals selected from Cu, Ag, and Au are preferred.

[0081] The metal element constituting the cationic polynuclear metal complex is not particularly limited as long as it is one or more transition metals B other than metal A, and transition metal B may be a metal selected from Group 11 of the periodic table so long as it does not overlap with metal A constituting the polynuclear metal complex. As transition metal B, one or more selected from Pd, Ni, Zn, Pt, Cd, Cu and Mn are preferred.

[0082] The ligand constituting the cationic polynuclear metal complex is not particularly limited as long as it can form a metal complex by coordinate bonding with a metal atom. For example, it may include one or more ligands selected from a tripodal phosphine and an amino acid having a thiol group, and a combination of a tripodal phosphine and an amino acid having a thiol group is preferred.

[0083] When a tripodal phosphine and an amino acid having a thiol group are contained as ligands, the ratio of the tripodal phosphine to the amino acid having a thiol group (tripodal phosphine / amino acid having a thiol group) is preferably 1 / 3 to 1 / 2.

[0084] Tripodal phosphines include, for example, tris(diphenylphosphinoalkyl)alkanes, such as 1,1,1-tris(diphenylphosphinomethyl)ethane. Examples of the amino acid having a thiol group include the same as those mentioned above, and among them, penicillamine is preferable. A preferred combination of a tripodal phosphine and an amino acid having a thiol group is a combination of 1,1,1-tris(diphenylphosphinomethyl)ethane and penicillamine.

[0085] The cationic polynuclear metal complex is preferably an accumulation of one or more polynuclear metal complexes consisting of an ion of a metal A selected from Group 11 of the periodic table, one or more transition metals B other than the metal A, and one or more ligands selected from an amino acid having a tripodal phosphine and a thiol group, and more preferably an accumulation of one or more polynuclear metal complexes consisting of an ion of a metal A selected from Group 11 of the periodic table, one or more transition metals B other than the metal A, and a ligand containing an amino acid having a tripodal phosphine and a thiol group. For example, such a polynuclear metal complex is formed by linking a sulfur atom of an amino acid having a thiol group to a metal A (e.g., Au), which is further crosslinked to a tripodal phosphine to form a trinuclear metal complex, and two of the trinuclear metal complexes are further crosslinked to three transition metal B ions (e.g., Cu ions) using an amino acid having a thiol group to form a nonanuclear metal complex. Then, with the nonanuclear metal complex being one unit, for example, 12 nonanuclear metal complexes are linked by eight metal B ions (e.g., Cu) to form a cationic 116-nuclear metal complex. This cationic 116-nuclear metal complex has a structure in which the eight transition metal B ions (e.g., Cu ions) of the nonanuclear metal complex are arranged at the vertices of a simple cubic lattice, and the structure is assembled as one unit. Furthermore, simultaneously with the formation of the cationic 116-nuclear metal complex, the trinuclear metal complex is crosslinked to three transition metal B ions (e.g., Cu ions) using an amino acid having a thiol group, and three more transition metal B ions (e.g., Cu ions) are coordinated to the crosslinked sites to form a 12-nuclear metal complex. The 12-nuclear metal complex is treated as one unit, and for example, 12 12-nuclear metal complexes are linked by 8 metal B ions (e.g., Cu) to form a cationic 152-nuclear metal complex, which can be mixed with the cationic 116-nuclear metal complex.

[0086] The cationic polynuclear metal complexes that give such a structure include polynuclear metal complexes represented by the following formula (11), and can form an ionic solid represented by the following formula (12).

[0087] [M 116M 12 h (X 11 ) ma (X 12 ) 3ma ] na (11)

[0088] (In the formula, M 11 represent, independently of each other, an ion of a metal A selected from Group 11 of the Periodic Table, M 12 each independently represents a transition metal B other than metal A, X 11 represent, independently of one another, a tripodal phosphine, X 12 each independently represents an amino acid having a thiol group, h represents 3 or 6; ma represents 1 or 2; and na represents an integer from 1 to 12.

[0089] [{M 11 6M 12 h (X 11 ) ma (X 12 ) 3ma} na (M 12 p M 13 q )](E) r (12)

[0090] (In the formula, M 11 represent, independently of each other, an ion of a metal A selected from Group 11 of the Periodic Table, M 12 each independently represents a transition metal B other than metal A, M 13 each independently represents a metal other than metal A, X 11 represent, independently of one another, a tripodal phosphine, X 12 each independently represents an amino acid having a thiol group, h represents 3 or 6; ma represents 1 or 2; na represents an integer from 1 to 18; E represents an anion or an inorganic acid; p, q, and r each independently represent an integer of 0 or 1 or more, provided that p, q, and r cannot simultaneously be 0.

[0091] M 11 an ion of a metal A selected from Group 11 of the periodic table, M 12 Transition metal B other than metal A, X 11 Tripod phosphines according to X 12 Specific examples of the thiol group-containing amino acid of the above-mentioned formula (1) include the same as those mentioned above, and when there are a plurality of such amino acids, they may be the same or different. M 13 Examples of the metal other than metal A include Na, Cd, etc., and when a plurality of metals are present, they may be the same or different. ma is 1 or 2 and can be appropriately selected. Although na is an integer of 1 to 18, 1 to 15 is preferable, and 1 to 12 is more preferable. The anion associated with E is not particularly limited, but may be, for example, Cl. - , Br - , F - , O 2- , S 2- , Te 2- , N3 - , NO3 - , ClO4 - , BF4 - , SiF6 2- , SO4 2- , PF4 - Examples of the inorganic acid include nitric acid, sulfuric acid, hydrochloric acid, chloric acid, and phosphoric acid. p, q, and r each independently represent an integer of 0 or 1 or more, with p being preferably 1 to 30, and more preferably 1 to 20, and q being preferably 1 to 30, and more preferably 1 to 20, and r being preferably 1 to 30, and more preferably 1 to 20. However, p, q, and r cannot be 0 at the same time.

[0092] The ionic solid according to this embodiment can be produced by any suitable method, for example, by reacting a ligand with a salt of metal A in a solvent to obtain a polynuclear metal complex, then reacting the polynuclear metal complex with a salt of transition metal B in a solvent to obtain an ionic solid having a cationic polynuclear metal complex as a crystal lattice, and then accumulating this polynuclear metal complex to produce an ionic solid in which the cationic polynuclear metal complex is accumulated. The organic solvent is not particularly limited as long as it is water-soluble, and for example, alcohol such as methanol or ethanol can be used. Furthermore, by immersing the obtained ionic solid in an aqueous solution of a salt of a metal other than metal A, a new ionic solid in which metal A ions have been exchanged for other metal ions can be produced.

[0093] The ionic solid according to this embodiment can be applied to various applications described in the first embodiment by incorporating various substances into the voids, but it is preferable to use it as a reaction field providing material. Here, in this specification, the "reaction field" refers to a place where a chemical reaction is carried out in a void, which is a nanospace. The reaction carried out in the voids of the ionic solid is not particularly limited and can be appropriately selected depending on the substance incorporated or the substance produced by the chemical reaction in the voids, and examples of the reaction include condensation, polymerization reaction, hydrolysis reaction, oxidation reaction, reduction reaction, elimination reaction, and rearrangement reaction. More specifically, for example, an ionic solid is immersed in a solution containing molybdate ions, which are oxoanions, to incorporate molybdate ions into the voids in the ionic solid, and the voids are used as a reaction field for a condensation reaction, and the molybdate ions are condensed to produce an ionic solid containing a polyacid. The oxoanion used here is not particularly limited as long as it is a metal oxoanion, but examples thereof include tungstic acid, molybdic acid, vanadic acid, manganic acid, perrhenic acid, chromic acid, etc. Furthermore, the polyacid can be produced from one type of metal oxoanion or multiple types of metal oxoanions. Furthermore, the polyacid clathrate ionic solid can also be used in an oxidation reaction. That is, by reacting the polyacid clathrate ionic solid and an oxidizing agent with a solution containing a substance to be oxidized, the oxidizing agent in the voids oxidizes the substance to be oxidized using the polyacid as a catalyst, and an oxide of the substance to be oxidized can be produced. In this way, an oxide can be produced by using the voids of the ionic solid according to this embodiment as a reaction field for an oxidation reaction. The oxidation reaction can be carried out at room temperature (20±15° C.) and normal pressure (atmospheric pressure), and does not require heating or cooling, or pressurization or decompression, so that it can be carried out efficiently with low energy consumption. In addition, the types of the oxidizing agent and the substance to be oxidized are not particularly limited and can be selected appropriately, and the amounts used can be set appropriately depending on the types of the oxidizing agent and the substance to be oxidized. The substance thus produced by chemical reaction in the voids of the ionic solid can be utilized not only as a reaction field due to the substance taken into the voids, but also for the above-mentioned applications. EXAMPLES

[0094] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0095] (1)X-ray structural analysis Equipment: Mercury 2 (Rigaku) ·X-ray source: Synchrotron radiation (SPring-8) 0.7000Å Measurement range: 2θ=1~59° Measurement interval: 1° Scanning speed: 20° / min Light intensity: 1010 photons / sec

[0096] (2) Nuclear magnetic resonance 1 1 H NMR was measured at room temperature using ECS500 (500 MHz) manufactured by JEOL Ltd.

[0097] (3) Raman spectroscopy The Raman spectroscopy was performed at room temperature using a JASCO NR-1800 (excitation light 523 nm semiconductor laser). The presence of iodine was detected at 100 to 300 cm -1 The presence or absence of a peak and the maximum wavelength were used to confirm this.

[0098] (Synthesis Example 1) Synthesis of Na3[Co2Au3(D-pen)6]2·13H2O 2.5g of D-pen (D-penicillamine) was suspended in 40ml of methanol, to which 3.4g of tetrachloroauric acid solution and 2mL of 2,2´-thiodiethanol were added and stirred, and then 3.8mL of 28% ammonia water was added and left at room temperature overnight, and then filtered to obtain crystals. 6mL of 1M sodium acetate solution and 430mg of sodium tricarbonatocobaltate (III) were added to 100mL of an aqueous solution containing 1g of this crystal, and the mixture was stirred at room temperature for 1 hour. 30mL of methanol was added to the purple solution, which was then left at room temperature overnight, filtered, and dried to obtain crystals of Na3[Co2Au3(D-pen)6]·13H2O. The isolated yield was 788mg (71%).

[0099] (Synthesis Example 2) Synthesis of [Co(H2O)6]3[Co2Au3(D-pen)6]2·nH2O (hereinafter referred to as "Co3D") A 1M aqueous solution of NH4Cl (400 μL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (100 mg, 0.0602 mmol) in H2O (3 mL). The solution was stirred at room temperature for 10 min, and then a pink solution of Co(OAc)2·4H2O (26 mg, 0.10 mmol) in water (1.6 mL) was added. After stirring at room temperature for a few minutes, the mixture was left at room temperature for 12 h. The resulting purple plate crystals were collected by filtration. X-ray analysis confirmed that the obtained crystals were the ionic solid represented by the above formula. The synthesis scheme of Co3D is shown in Figure 1, and the crystal structure of the ionic solid is shown in Figure 2. The isolated yield was 48 mg (39%). The opening diameter of the pores of Co3D was 3.5 nm, and the porosity was 80%.

[0100] (Synthesis Example 3) Synthesis of Na9[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·nH2O (hereinafter referred to as "Zn1D") The Na3[Co2Au3(D-pen)6)·13H2O (50 mg, 0.030 mmol) from Synthesis Example 1 was dissolved in sodium acetate buffer (2.5 mL, pH 5.5, [OAc - ]=0.9M) to give a purple solution, and Zn(OAc)2·2H2O (10 mg, 0.045 mmol) was dissolved in a NaOAc buffer solution (2.5 mL, pH 5.5, [OAc - A colorless solution of Zn1D (0.9M) was added. The mixture was stirred at room temperature for 5 minutes to obtain a dark purple solution. The reaction solution was left at room temperature for 2 weeks, and then purple hexagonal columnar crystals were filtered out. As in Synthesis Example 1, the obtained crystals were confirmed to be the ionic solid represented by the above chemical formula by X-ray analysis. The synthesis scheme of Zn1D is shown in Figure 1, and the crystal structure of the ionic solid is shown in Figure 3. The isolated yield was 14 mg (23%). The opening diameter of the pores in Zn1D was 2 nm, and the porosity was 60%.

[0101] (Synthesis Example 4) Synthesis of [Co(en)3][Co2Au3(D-pen)6]·nH2O A yellow solution of rac-[Co(en)3](NO3)3 (7.1 mg, 0.017 mmol) in water (10 mL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (30 mg, 0.018 mmol) dissolved in H2O (10 mL). The solution was stirred at room temperature for 10 min, and the mixture was left at room temperature for 2 months. The resulting purple hexagonal columnar crystals were collected by filtration. X-ray analysis confirmed that the obtained crystals were the ionic solid represented by the above chemical formula. The isolated yield was 16 mg (43%). The pore opening diameter of the ionic solid was 2 nm, and the porosity was 60%.

[0102] (Synthesis Example 5) Synthesis of [Co(tn)3][Co2Au3(D-pen)6]·nH2O A yellow solution of rac-[Co(tn)3]Cl3 (25 mg, 0.064 mmol) in water (10 mL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (100 mg, 0.0602 mmol) dissolved in H2O (10 mL). The solution was stirred at room temperature for 5 min, and the mixture was left at room temperature for 10 days. The resulting purple hexagonal columnar crystals were collected by filtration. X-ray analysis confirmed that the obtained crystals were the ionic solid represented by the above chemical formula. The isolated yield was 25 mg (22%). The pore opening diameter of the ionic solid was 2 nm, and the porosity was 60%.

[0103] (Synthesis Example 6) [Na 10 (OAc)(HO) 30 Synthesis of ][Co2Au3(D-pen)6]3·nH2O After stirring a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (100 mg, 0.0602 mmol) in sodium acetate buffer (0.5 M, pH 6.0), the mixture was left at room temperature for 12 h, and the resulting crystals were collected by filtration. The isolated yield was 40 mg. The pore opening diameter of the ionic solid was 2.7 nm, and the porosity was 79%.

[0104] Synthesis of hydrophilic substance-encapsulated Co3D Example 1 10 mg of the Co3D crystal obtained in Synthesis Example 2 was immersed in 0.15 mol of ethylene glycol as a hydrophilic substance (guest compound) and left at room temperature for 2 days. It was then washed with a large amount of ethanol to obtain an ionic solid containing the guest compound as purple crystals. 1 The amount of the hydrophilic substance (guest compound) shown in Table 1 was quantitatively analyzed by H NMR (DO). 1The number of hydrophilic substances (guest compounds) per penicillamine complex was determined by comparing the integral value of the methyl group protons of penicillamine and the integral value of the protons of the hydrophilic substances (guest compounds) in the H NMR chart, and was converted into the inclusion amount (mass%) of the hydrophilic substances (guest compounds) from the following formula (i). The results are also shown in Table 1.

[0105] Inclusion amount (mass%)=100×P×Q / 1842.5+(P×Q) (i)

[0106] (In formula (i), P represents the molecular weight of the hydrophilic substance (guest compound), and Q represents the number of hydrophilic substances (guest compounds).)

[0107] Example 2 The same procedure as in Example 1 was carried out except that water in which 0.9 M sucrose was dissolved was used instead of ethylene glycol in Example 1, to obtain an ionic solid in which a guest compound was encapsulated. The amount of encapsulation was then calculated. The results are shown in Table 1.

[0108] Example 3 The same procedure as in Example 2 was carried out except that 0.3 M mannitol was used instead of 0.9 M sucrose in Example 2, to obtain an ionic solid encapsulating a guest compound. The encapsulation amount was then calculated. The results are shown in Table 1.

[0109] Example 4 The same procedure as in Example 1 was carried out except that a water-ethanol solution (water / ethanol = 1 / 4) in which 1 M arabitol was dissolved was used instead of ethylene glycol in Example 1, to obtain an ionic solid in which a guest compound was encapsulated, and the amount of encapsulation was calculated. The results are shown in Table 1.

[0110] Example 5 An ionic solid containing a guest compound was obtained by the same procedure as in Example 4, except that xylitol was used instead of arabitol. The amount of the guest compound was then calculated. The results are shown in Table 1.

[0111] Example 6 An ionic solid encapsulating a guest compound was obtained by the same procedure as in Example 4, except that adonitol was used instead of arabitol. The encapsulation amount was then calculated. The results are shown in Table 1.

[0112] Example 7 The same procedure as in Example 1 was carried out, except that a water-ethanol solution (water / ethanol = 1 / 3) containing 0.1 M D-penicillamine was used instead of ethylene glycol, to obtain an ionic solid containing a guest compound. The amount of inclusion was then calculated. The results are shown in Table 1.

[0113] Example 8 An ionic solid encapsulating a guest compound was obtained by the same procedure as in Example 7, except that L-penicillamine was used instead of D-penicillamine. The encapsulation amount was then calculated. The results are shown in Table 1.

[0114] Example 9 The same procedure as in Example 1 was carried out, except that a water-ethanol solution (water / ethanol = 1 / 1) in which 0.05 M D-aspartic acid was dissolved was used instead of ethylene glycol, to obtain an ionic solid in which a guest compound was encapsulated. The amount of encapsulation was then calculated. The results are shown in Table 1.

[0115] Example 10 An ionic solid encapsulating a guest compound was obtained by the same procedure as in Example 9, except that 0.15M α-cyclodextrin was used instead of 0.05M D-aspartic acid. The encapsulation amount was then calculated. The results are shown in Table 1. The encapsulation amount (%) of cyclodextrin was calculated as follows: 1 The integral value of the methyl group of penicillamine and the integral value of the methine group of cyclodextrin in the 1 H NMR chart were compared, and the inclusion amount of cyclodextrin was converted into the amount per penicillamine complex.

[0116] Example 11 An ionic solid encapsulating a guest compound was obtained by the same procedure as in Example 10, except that β-cyclodextrin was used instead of α-cyclodextrin. The encapsulation amount was then calculated. The results are shown in Table 1.

[0117] Example 12 The same procedure as in Example 10 was carried out except that γ-cyclodextrin was used instead of α-cyclodextrin in Example 10, to obtain an ionic solid encapsulating a guest compound, and the encapsulation amount was determined. The results are shown in Table 1. When the ionic solid shown in Synthesis Example 6 was used in place of Co3D in Example 12, it was confirmed that two molecules of γ-cyclodextrin were included.

[0118] (Reference example 1) The same procedure as in Example 1 was carried out, except that ethylene glycol was replaced with water containing 10M formaldehyde. However, after leaving the mixture for 2 days, 1 Since no signal for the guest compound was observed in the H NMR spectrum, it was determined that the guest compound was not included. The results are shown in Table 1.

[0119] (Reference example 2) The same procedure as in Reference Example 1 was carried out, except that a water-ethanol solution (water / ethanol=1 / 4) containing 14 M ethanol was used instead of formaldehyde. However, after leaving it for 2 days, 1 Since no signal for the guest compound was observed in the H NMR spectrum, it was determined that the guest compound was not included. The results are shown in Table 1.

[0120] [Table 1]

[0121] Synthesis of hydrophilic substance-encapsulated Zn1D Example 13 An ionic solid encapsulating a guest compound was obtained as a purple solid by the same procedure as in Example 1, except that 10 mg of Zn1D crystals obtained in Synthesis Example 3 was used instead of Co3D in Synthesis Example 1 as the host compound. 1 The amount of the hydrophilic substance (guest compound) shown in Table 2 was quantitatively analyzed by H NMR (DO). 1 The number of hydrophilic substances (guest molecules) per penicillamine complex was determined from the H NMR chart, and was converted into the inclusion amount (mass%) of the hydrophilic substance (guest compound) from the following formula (ii). The results are shown in Table 2.

[0122] Inclusion amount (mass%)=100×P×Q / 1721.5+(P×Q) (ii)

[0123] [In formula (ii), P represents the molecular weight of the hydrophilic substance (guest compound), and Q represents the number of hydrophilic substances (guest compounds)]

[0124] Example 14 The same procedure as in Example 13 was carried out except that a water-ethanol solution (water / ethanol = 1 / 4) in which 1M xylitol was dissolved was used instead of ethylene glycol in Example 13, to obtain an ionic solid in which a guest compound was encapsulated. The amount of encapsulation was then calculated. The results are shown in Table 2.

[0125] Example 15 The same procedure as in Example 14 was carried out except that adonitol was used instead of xylitol in Example 14, to obtain an ionic solid containing a guest compound. The amount of the guest compound was then calculated. The results are shown in Table 2.

[0126] (Example 16) The same procedure as in Example 13 was carried out, except that a water-ethanol solution (water / ethanol = 1 / 1) in which 0.15 M α-cyclodextrin was dissolved was used instead of ethylene glycol, to obtain an ionic solid in which a guest compound was encapsulated. The amount of encapsulation was then calculated. The results are shown in Table 2. The amount of encapsulation of cyclodextrin (%) was calculated as follows:1 The integral value of the methyl group of penicillamine and the integral value of the methine group of cyclodextrin in the 1 H NMR chart were compared, and the inclusion amount of cyclodextrin was converted into the amount per penicillamine complex.

[0127] (Example 17) The same procedure as in Example 16 was carried out except that β-cyclodextrin was used instead of α-cyclodextrin in Example 16, to obtain an ionic solid containing a guest compound. The amount of the guest compound was then calculated. The results are shown in Table 2.

[0128] (Example 18) The same procedure as in Example 16 was carried out except that γ-cyclodextrin was used instead of α-cyclodextrin in Example 16, to obtain an ionic solid containing a guest compound. The amount of the guest compound was then calculated. The results are shown in Table 2.

[0129] (Reference example 3) The same procedure as in Example 13 was carried out, except that a water-ethanol solution (water / ethanol = 1 / 4) in which 10 M formaldehyde was dissolved was used instead of ethylene glycol. However, after leaving it for 2 days, 1 Since no signal for the guest compound was observed in the H NMR, it was determined that the guest compound was not included. The results are shown in Table 2.

[0130] (Reference example 4) The same procedure as in Comparative Example 3 was carried out, except that a water-ethanol solution (water / ethanol=1 / 4) containing 14 M ethanol was used instead of formaldehyde in Reference Example 3. However, after leaving it for 2 days, 1 Since no signal for the guest compound was observed in the H NMR, it was determined that the guest compound was not included. The results are shown in Table 2.

[0131] [Table 2]

[0132] (Example 19) Further, iodine was included to synthesize α-cyclodextrin-incorporated Co3D (CoD+α-CD+I2). 50 mg of the Co3D crystal obtained in Synthesis Example 1 was immersed in 0.5 mL of ethylene glycol solution containing 0.15 mol of α-cyclodextrin dissolved therein and 0.1 mol of iodine dissolved therein, and left at room temperature for one day. After that, it was washed with an aqueous methanol solution to obtain a brownish purple ionic solid. The iodine uptake of the obtained ionic solid was analyzed by Raman spectroscopy and 1 The sample was analyzed by H NMR (D2O). The Raman spectroscopic analysis was performed using NR-1800 manufactured by JASCO Corporation. The results are shown in Figures 4 and 5. These analyses confirmed that iodine was included in the α-cyclodextrin-incorporated Co3D. Next, the amount of iodine included was examined using fluorescent X-ray analysis. For the fluorescent X-ray analysis, an energy dispersive fluorescent X-ray analyzer EDX-720 (manufactured by SHIMADZU) was used as the fluorescent X-ray analyzer. The fluorescent X-ray analysis revealed that [Co2Au3]:I2 = 1:0.35. The amount of iodine included was determined by observing the specific X-ray fluorescence of iodine and comparing its intensity with the fluorescent X-ray intensity of cobalt.

[0133] (Example 20) Further, iodine was included to synthesize α-cyclodextrin-incorporated Zn1D (Zn1D + α-CD + I2). An ionic solid was obtained by the same procedure as in Example 19, except that 50 mg of the Zn1D crystals obtained in Synthesis Example 2 was used. The iodine uptake of the obtained ionic solid was analyzed by Raman spectroscopy and 1 The result was analyzed by H NMR (D2O). The results are shown in Figures 4 and 5. These analyses confirmed that iodine was included in the α-cyclodextrin-inclusion Zn1D. Next, the amount of iodine included was examined by X-ray fluorescence analysis in the same manner as in Example 19, and it was found to be [Co2Au3]:I2=1:0.8.

[0134] Example 21 Synthesis of Na9[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·1EG·13H2O 20 mg of the Na9[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·nH2O crystals obtained in Synthesis Example 2 were immersed in 0.5 mL of ethylene glycol (99.5%) and left at room temperature for 3 days. The purple solid was washed with methanol and dried for several hours to obtain Na9[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·1EG·13H2O. The amount of ethylene glycol included is as follows: 1 The intensity was calculated by comparing the integral intensity of the methylene hydrogen signal (3.65 ppm, 4H) of ethylene glycol with the integral intensity of the methyl group hydrogen signals (1.5 ppm, 18H and 1.6 ppm 18H) of the complex anion in H NMR. Also, Na + The amount of ions is 23 The Na NMR resonance intensity was quantified by creating a calibration curve using standard samples (0.1 mM, 1 mM, 10 mM, and 100 mM NaCl / D2O solutions).

[0135] Example 22 Na9[{Zn(OAc)2}{Co2Au3( D Synthesis of -pen)6}3]·4EG·13H2O Na9[{Zn(OAc)2}{Co2Au3(D-pen)6}3] 4EG 13H2O was obtained by the same procedure as in Example 21, except that 0.5 mL of ethylene glycol (99.5%) was used and the mixture was left at room temperature for 5 days. The amount of ethylene glycol included was determined by the same procedure as in Example 21.

[0136] (Example 23) Synthesis of Na2Cs7[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·4EG·10H2O Na3[Co2Au3(D-pen)6]·13H2O (100 mg) was dissolved in acetic acid / cesium acetate buffer solution (5 mL, pH 6, [OAc -]=0.5M) and Zn(OAc)2·2H2O (4.4 mg) was added to an aqueous acetic acid / cesium acetate buffer solution (5 mL, pH 6, [OAc - ]=0.5M) was added and stirred at room temperature for 5 minutes to obtain a dark purple solution. After leaving the solution at room temperature for 3 weeks, the purple hexagonal columnar crystals were filtered out to obtain Na2Cs7[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·0EG. The isolated yield was 21 mg (20%). The obtained crystals (20 mg) were immersed in 0.5 mL of ethylene glycol (99.5%) and left at room temperature for 3 days. The purple solid was washed with methanol and dried for several hours to obtain Na2Cs7[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·1EG·10H2O. Ethylene glycol inclusion amount, Na + The amount of ions was determined in the same manner as in Example 21.

[0137] (Measurement of ionic conductivity) The ionic conductivity of the ionic solids obtained in Examples 21 to 23 was measured by the following method. For the ionic solids of Examples 21 and 22, a comparative experiment was carried out using Na9[{Zn(OAc)2}Co2Au3(D-pen)6]·13H2O, which does not include ethylene glycol, as Reference Example 5, and for the ionic solid of Example 23, a comparative experiment was carried out using Na2Cs7[{Zn(OAc)2}{Co2Au3(D-pen)6}3]·10H2O, which does not include ethylene glycol, as Reference Example 6.

[0138] (1) Preparation of pellets Approximately 10 to 20 mg of powder or crystalline specimen was packed into a cylindrical cell with a diameter of 3 mm and held at a pressure of 5 GPa for more than 20 minutes to produce a pellet.

[0139] (2) Measurement of ionic conductivity The pellets obtained were crimped onto a Toyo Corporation SH-Z cell holder. The entire cell holder with the cable connected was placed in a thermostatic chamber with controlled humidity and temperature. In this state, AC impedance measurements were performed using a pseudo four-terminal method in the frequency range of 500 kHz to 20 Hz using a Wayne Kerr 6430B Component Analyzer. A Nyquist plot was created for the obtained AC impedance, with the real part (Z') on the horizontal axis and the imaginary part (Z") on the vertical axis, and a semicircular shape due to bulk ionic conduction was observed. The diameter of this plot was regarded as the bulk resistance (R) due to ionic conduction, and the resistivity of the entire specimen was calculated. The ionic conductivity (σ / Scm) of each sample at 25°C and RH 69% was -1 The measurement results are shown in Table 3.

[0140] [Table 3]

[0141] (Example 24) Synthesis of [Ni(H2O)6]3[Co2Au3(D-pen)6]2·nH2O (hereinafter referred to as "Ni3D") A green solution of Ni(OAc)2·4H2O (26 mg, 0.09 mmol) in water (1 mL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (100 mg, 0.0602 mmol) in H2O (4 mL). After stirring for a few minutes at room temperature, the mixture was left at room temperature for 1 day. The resulting purple plate crystals were collected by filtration. X-ray analysis confirmed that the obtained crystals were the ionic solid represented by the above formula. The crystal structure of the ionic solid is shown in Figure 6. The isolated yield was 21 mg (20%). The opening diameter of the pores of Ni3D was 3.5 nm, and the porosity was 80%.

[0142] (Example 25) Synthesis of [Mn(H2O)6]3[Co2Au3(D-pen)6]2·nH2O (hereinafter referred to as "Mn3D") A light pink solution of Mn(OAc)2·4H2O (22 mg, 0.09 mmol) in water (1 mL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (100 mg, 0.0602 mmol) in H2O (1 mL). After stirring for a few minutes at room temperature, the mixture was left at room temperature for 3 days. The resulting purple plate crystals were collected by filtration. X-ray analysis confirmed that the crystals were the ionic solid represented by the above formula. The isolated yield was 15 mg (15%). The opening diameter of the pores of Mn3D was 3.5 nm, and the porosity was 80%.

[0143] (Example 26) Synthesis of [Ni(H2O)6]2[Ni(H2O)4] [Co2Au3(D-pen)6]2·nH2O (hereinafter referred to as "Ni1D") A green solution of Ni(OAc)2·4H2O (11 mg, 0.045 mmol) in water (2.5 mL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (50 mg, 0.0301 mmol) in H2O (2.5 mL). After stirring for a few minutes at room temperature, the mixture was left at room temperature for 3 days. The resulting purple hexagonal columnar crystals were collected by filtration. X-ray analysis confirmed that the obtained crystals were the ionic solid represented by the above chemical formula. The crystal structure of the ionic solid is shown in Figure 7. The isolated yield was 21 mg (35%). The opening diameter of the Ni1D pores was 2 nm, and the porosity was 60%.

[0144] Example 27 Synthesis of [Mn(H2O)6]2[Mn(H2O)4] [Co2Au3(D-pen)6]2·nH2O (hereinafter referred to as "Mn1D") A light pink solution of Mn(OAc)2·4H2O (11 mg, 0.045 mmol) in water (2.5 mL) was added to a purple solution of Na3[Co2Au3(D-pen)6]·13H2O (50 mg, 0.0301 mmol) in H2O (2.5 mL). After stirring for a few minutes at room temperature, the mixture was left at room temperature for 3 days. The resulting purple hexagonal columnar crystals were collected by filtration. X-ray analysis confirmed that the crystals were the ionic solid represented by the above formula. The isolated yield was 23 mg (39%). The opening diameter of the pores of Mn1D was 2 nm, and the porosity was 60%.

[0145] Examination as a gas adsorption material (Example 28) The adsorption amounts of nitrogen and carbon dioxide were measured using the α-cyclodextrin-incorporated Co3D (CoD+α-CD) obtained in Example 10 and the Co3D obtained in Synthesis Example 2 as samples. The measurements were performed by weighing out 10 mg of the sample, holding it for 2 hours under conditions of a temperature of 120°C and a pressure of 0.1 Pa, and then using a Microtrackbell BELSORP-max, nitrogen adsorption was performed at 77 K and carbon dioxide adsorption was performed at 200 K. The results are shown in FIG. 8 as the adsorption amount per [Co2Au3] at the pressure P / P0 during measurement relative to normal pressure. From FIG. 8, it can be seen that the adsorption ability of nitrogen and carbon dioxide is improved by inclusion of α-cyclodextrin in Co3D.

[0146] Examination as a solvent vapor adsorption material (Example 29) The amount of adsorption of ethanol vapor and water vapor was measured using the Mn3D obtained in Example 25 as a sample. The measurement was performed by weighing out 10 mg of the sample, holding it at room temperature and a pressure of 0.1 Pa for 2 hours, and then using a Microtrackbell BELSORP-max, the adsorption of ethanol vapor and water vapor was performed at 298 K. The results are shown in FIG. 9 as the amount of adsorption per [Co2Au3] at the pressure P / P0 during measurement relative to normal pressure. In FIG. 9, the black circles indicate the adsorption of water vapor, the white circles indicate the desorption of water vapor, the black squares indicate the adsorption of ethanol vapor, and the white squares indicate the desorption of ethanol vapor. From FIG. 9, it can be seen that almost no ethanol vapor is adsorbed, water vapor can be selectively adsorbed, and desorption is also easy.

[0147] (Example 30) (1)[[Au6Cu3(tdme)2(D-pen)6)] 12 Cu)8](NO3) 16 Synthesis of 25Cu(NO3)2 324H2O

[0148] 2.5g of tetrachloroauric(III) acid was dissolved in 50mL of water / methanol mixed solvent (2:3), and a solution of 2.3mL of 2,2'-thiodiethanol dissolved in 2.5mL of methanol was added to this solution to prepare a colorless solution. When a solution of 1.3g of tdme (1,1,1-tris(diphenylphosphinomethyl)ethane) dissolved in 25mL of chloroform / methanol mixed solvent (4:1) was added to the prepared colorless solution, a white solid was immediately precipitated. After stirring at room temperature for 6 hours in the dark, 100mL of cooled methanol was added, and the mixture was left standing in the dark for a day, filtered, washed with 250mL, and dried under reduced pressure to obtain 2.6g of white solid [Au3(tdme)Cl3]. The isolation yield was 96%.

[0149] Next, 2.00 g of [Au3(tdme)Cl3] was suspended in 100 mL of ethanol, to which 0.68 g of D-penicillamine (D-pen) was added, and the mixture was stirred at room temperature for 1 hour. The slightly dissolved and unreacted [Au3(tdme)Cl3] was filtered off, and 45 mL of 0.10 M aqueous sodium hydroxide solution was added to the resulting colorless solution. This solution was concentrated to dryness, and the resulting white powder was washed three times with 40 mL of water and dried under reduced pressure to obtain 2.37 g of the product [Au3(tdme)( D -pen)3]5H2O was obtained. The isolated yield was 90%. The resulting product [Au3(tdme)( D The structure of -pen)3]5H2O is 1 H-NMR, 31 The results were confirmed by P-NMR, IR and elemental analysis.

[0150] · 1 H-NMR spectrum (ppm from TMS, methanol-d4): δ 0.99 (s, 3H), 1.33 (s, 9H), 1.67 (s, 9H), 3.47 (s, 3H), 7.53-7.54 (m, 18H), 7.65-7.70 (m, 6H), 7.76-7.80 (m, 6H) · 31 P-NMR spectrum (ppm from H3PO4, methanol-d4): δ 22.1 (s) IR spectrum (cm- 1 , KBr disk): 1627 (COO-) ·Anal. Calcd for [Au3(tdme)(D-Hpen)3]·5H2O = C 56 H 79 N3O 11 P3S3Au3: C, 38.43; H, 4.55; N, 2.40%. Found: C, 38.34; H, 4.49; N, 2.38%

[0151] Furthermore, 1.00 g of [Au3(tdme)(D-pen)3] was suspended in 100 mL of ethanol, to which 17.2 mL of 0.1 M sodium hydroxide solution and 17.2 mL of 0.1 M cadmium nitrate solution were added, and the mixture was stirred at room temperature for 6 hours to obtain a colorless solution. This solution was concentrated to a total volume of 50 mL, and allowed to naturally concentrate at room temperature for several days to obtain colorless crystals of [[Au6Cd3(tdme)2(D-pen)6] 12 Cd4Na)4](NO3) 12 0.83 g of 4Cd(NO3)2 432H2O was obtained. The isolated yield was 64%.

[0152] Next, the colorless crystals obtained above were immersed in a 1M copper nitrate solution for about 5 days, and green crystals [[Au6Cu3(tdme)2(D-pen)6] 12 Cu)8](NO3) 16 An ionic solid was obtained, represented by the formula: ·25Cu(NO3)2·324H2O (hereinafter referred to as the "116-nuclear complex"). The pore size of the ionic solid was 0.8 nm, and the porosity was 40%. In addition, when 1M cobalt nitrate was used instead of the 1M copper nitrate solution, [[Au6Co3(tdme)2(D-pen)6]12Co8](NO3) 16 We obtained an ionic solid represented by the formula: ·25Co(NO3)2·324H2O. The pore size of this ionic solid was 0.9 nm, and the porosity was 41.9%.

[0153] (2) Crystal structure analysis Single-crystal X-ray diffraction was performed on a good-quality single crystal of (1). In the crystal, the sulfur atom of the D-pen ligand was linked to a gold ion [Au(D-pen)] - A trinuclear gold complex unit ([Au3(tdme)(D-pen)3]) in which three units are bridged by a tripodal triphosphine ligand tdme. 3- ) is formed, and two of these trinuclear gold complex units are DThe -pen moiety was used to bridge three copper(II) ions to form an Au6Cu39 core complex ([Au6Cu3(tdme)2(D-pen)6]). The coordination environment around the copper ion was disordered in a 1:1 ratio into two types, an N2S2 type planar 4-coordination structure and an NOS2 type planar 4-coordination structure. Two carboxyl groups of the D-pen in the above Au6Cu39 core complex were coordinated to the copper ion, and the copper ion linked the three Au6Cu39 core complexes. A total of 12 Au6Cu39 core complexes were linked by eight copper ions to form a spherical Au 72 Cu 44 A 116-nuclear complex was formed. The nitrate anion was present as a counter anion in the gap surrounded by the phenyl groups on the outer surface of the complex. 72 Cu 44 The 116-nuclear complex was arranged in a simple cubic lattice, with large gaps between the spheres that were filled with copper hydrate and water molecules.

[0154] Study of reaction field providing material (1) Incorporation of metal oxoacid ions into the 116-nuclear complex (Example 31) The 116-nuclear complex obtained in Example 30 was immersed overnight in a 0.4M aqueous solution of sodium molybdate, and the crystals were collected by filtration. The IR spectrum of the obtained crystals showed that the peak intensity derived from nitrate anions was weaker than that of the spectrum before immersion, while the peak derived from molybdate ions was stronger, suggesting that anion exchange had occurred. Furthermore, a decrease in the number of nitrate anions was confirmed by CHN elemental analysis. The IR spectrum is shown in Figure 10.

[0155] Example 32 The crystals were collected in the same manner as in Example 31, except that sodium tungstate was used instead of the aqueous sodium molybdate solution. The IR spectrum was measured in the same manner as in Example 31, and the results are shown in FIG.

[0156] (Example 33) The crystals were collected in the same manner as in Example 31, except that sodium vanadate was used instead of the aqueous sodium molybdate solution. The IR spectrum was measured in the same manner as in Example 31, and the results are shown in FIG.

[0157] (2) Condensation reaction within the cavity of the 116-nuclear complex (Example 34) The 116-nuclear complex obtained in Example 30 was immersed in a 0.4M aqueous solution of sodium molybdate overnight, and 1M nitric acid was added to the reaction solution after immersion and left to stand overnight. Gold, copper, and molybdenum were detected from the fluorescent X-rays. The IR spectrum showed that the peaks derived from mononuclear molybdic acid before the reaction had disappeared, and new Mo6O 19 2- The crystals were dissolved in acetonitrile and subjected to ESI-mass spectrometry, which revealed a peak corresponding to Mo6O 19 2- and HMoO 19 - A signal consistent with the above was observed. The results are shown in FIG. In addition, when 1M nitric acid was added to the reaction solution after immersion and left to stand overnight (pH 5-7), Mo7O 24 6- However, when 1M nitric acid was added and the mixture was left standing overnight (pH 1-2), β-Mo8O 26 4- The IR analysis shown in FIG. 12 confirmed that each of the above was produced.

[0158] (3) Oxidation reaction using polyacid-inclusion 116-nuclear complex (Example 35) Condensed molybdic acid inclusion complex (Mo6O 19 2- A solution of 0.5 mg of the (116) nuclear complex and 500 μL of deuterated acetonitrile solvent, 5 μL of DMSO as the substrate, and 20 μL (2.5 equivalents) of hydrogen peroxide as the oxidizing agent was placed in an NMR tube. The reaction solution was stored at room temperature and was then analyzed at regular intervals. 1H-NMR was measured (JEOL RESONANCE ECA500). The reaction conversion rate was calculated from the integrated intensity ratio of the methyl group peaks of DMSO and DMSO2. In addition, as shown in Table 4, the molybdic acid clathrate ionic solid (MoO4 2- The same procedure was performed for the 116-nuclear complex and other catalysts, and the time course of the conversion per catalytic active site was plotted. The results are shown in Figure 13. In the above, the 116-nuclear complex is [[Au6Cu3(tdme)2(D-pen)6] 12 Cu)8](NO3) 16 means. Similarly, measurements were carried out for the substrates shown in Table 5. The results are shown in Figures 14 to 16.

[0159] [Table 4]

[0160] [Table 5]

Claims

1. An ionic solid having voids for incorporating a substance, the voids are formed by the crystal lattice of the metal complex; one or more selected from polyacids, inorganic salts, metal ions, oxoanions, and hydrophilic substances having a molecular weight of 60 or more are enclosed in the voids; Ionic solids.

2. 2. The ionic solid according to claim 1, wherein the hydrophilic substance is one or more selected from the group consisting of polyhydric alcohols having a molecular weight of 60 or more, cyclic oligosaccharides having a molecular weight of 60 or more, saccharides having a molecular weight of 60 or more, sugar alcohols having a molecular weight of 60 or more, and amino acids having a molecular weight of 60 or more.

3. 3. The ionic solid according to claim 1, wherein the voids occupy 40% or more of the crystal lattice.

4. 4. The ionic solid according to claim 1, wherein the opening diameter of the voids is 0.5 to 5 nm.

5. 5. The ionic solid according to claim 1, which is an electrochemical device material, a reaction field providing material, a gas adsorption material, a solvent vapor adsorption material, a molecular recognition material, a metal ion exchanger, or an anion exchanger.

6. A column packing material comprising the ionic solid according to any one of claims 1 to 5.

7. A catalyst support comprising the ionic solid according to any one of claims 1 to 5.

8. 6. The ionic solid according to claim 1, wherein the metal complex is an anionic metal complex (A) and a cationic species (B) arranged via a coordinate bond or an ionic bond.

9. (A) The anionic metal complex is a metal complex having two metals M which may be the same or different and are selected from the elements of Group 9 of the periodic table. 1 and three metals M, which may be the same or different, selected from the elements of Group 11 of the periodic table. 2 and M bonded via one ligand 1 M 2 9. The ionic solid of claim 8 which is a pentanuclear complex anion.

10. 10. The ionic solid of claim 9, wherein the ligand is an amino acid having a thiol group.

11. The ionic solid according to any one of claims 8 to 10, wherein the anionic metal complex (A) is a metal complex represented by the following general formula (1): [(M 1 ) d (M 2 ) e (X 1 ) f ] k- (1) (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table; X 1 represents an amino acid having a thiol group, d represents a number from 0 to 4, e represents a number from 0 to 4; f is a number from 1 to 8, k represents a number from 1 to 4. However, d and e cannot be 0 at the same time.)

12. The ionic solid according to any one of claims 8 to 11, wherein the cationic species (B) is a metal complex represented by the following general formula (2): A a [(M 3 ) l (X 2 ) m ] j (2) (In the formula, A represents an alkali metal ion or an alkaline earth metal ion; M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate, a represents a number from 0 to 10; l represents a number from 0 to 1, m is a number from 1 to 6, j represents a number from 1 to 3. However, a and l cannot be 0 at the same time.)

13. 13. The ionic solid of any one of claims 8 to 12, wherein the (B) cationic species comprises a cationic metal complex.

14. 14. The ionic solid according to claim 13, wherein the cationic metal complex is one or more selected from the following compound group α: <Compound group α> [Co(NH 3 ) 6 ] 3+ 、[Co(H 2 O)(NH 3 ) 5 ] 3+ 、[Co(NO 2 )(NH 3 ) 5 ] 2+ 、 [Co(H 2 O) 6 ] 2+ , [Ni(H 2 O) 6 ] 2+ , [Mn(H 2 O) 6 ] 2+ [Co(H 2 O) 4 ] 2+ 、 [Ni(H 2 O) 4 ] 2+ , [Mn(H 2 O) 4 ] 2+ 、{Li[Zn(OAc) 2 ]} + 、 {Na[Zn(OAc) 2 ]} + 、{K[Zn(OAc) 2 ]} + 、{Cs[Zn(OAc) 2 ]} + 、 {Na 2 Cs 7 [Zn(OAc) 2 ]} 9+ 、{Na 9 [Zn(OAc) 2 ]} 9+ 、 [Co(en) 3 ] 3+ [Co(tn) 3 ] 3+ (wherein OAc represents acetate ion, en represents ethylenediamine, and tn represents 1,3-diaminopropane.)

15. The ionic solid according to any one of claims 1 to 14, wherein the crystal lattice comprises a metal complex represented by the following general formula (3): [(M 1 ) 3 (M 2 ) 2 (X 1 ) 6 ] 2 [(M 3 )(X 2 ) m1 ] 3 ・nH 2 O (3) (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table; M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, or a carboxylate, m1 represents a number from 1 to 6; n is a number from 1 to 100.

16. The ionic solid according to any one of claims 1 to 14, wherein the crystal lattice comprises a metal complex represented by the following general formula (4): (A) a [(M 1 ) 3 (M 2 ) 2 (X 1 ) 6 ] b [(M 3 ) l (X 2 ) m2 ] c ・nH 2 O (4) (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table; M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, a nitrite ion, and a carboxylate; A's each independently represent an alkali metal ion or an alkaline earth metal ion; a represents a number from 0 to 10; b represents a number from 1 to 3; c represents a number from 1 to 3; l represents a number from 0 to 1, m2 represents a number from 1 to 6; n represents a number from 1 to 100.

17. The ionic solid according to any one of claims 1 to 14, wherein the crystal lattice comprises a metal complex represented by the following general formula (5): (A) 9 [(M 1 ) 3 (M 2 ) 2 (X 1 ) 6 ] 3 [(M 3 )(X 2 ) m3 ] 2 ・nH 2 O (5) (In the formula, M 1 each independently represents a metal element, which may be the same or different, selected from the elements of Group 9 of the periodic table, M 2 each independently represents a metal element, which may be the same or different, selected from the elements of Group 11 of the periodic table; M 3 represents a metal element selected from Groups 9 and 12 of the periodic table, X 1 each independently represents an amino acid having a thiol group, X 2 each independently represents one or more selected from water, an ammine, a diamine, or a carboxylate; A's each independently represent an alkali metal ion or an alkaline earth metal ion; m3 represents a number from 1 to 6, n is a number from 1 to 100.

18. An ionic solid according to any one of claims 1 to 17, which exhibits bulk ionic conductivity.

19. An ionic solid having voids for incorporating a substance, the voids are formed by the crystal lattice of the metal complex; The metal complex is an ionic solid, which is a cationic polynuclear metal complex in which polynuclear metal complexes each composed of a metal ion, a metal element, and a ligand are accumulated.

20. 20. The ionic solid according to claim 19, wherein the cationic polynuclear metal complex is a 9- to 200-nuclear cationic metal complex.

21. 21. The ionic solid according to claim 19 or 20, wherein the cationic polynuclear metal complex is an accumulation of one or more polynuclear metal complexes each comprising an ion of a metal A selected from Group 11 of the periodic table, one or more transition metals B other than said metal A, and one or more ligands selected from a tripodal phosphine and an amino acid having a thiol group.

22. The ionic solid according to any one of claims 19 to 21, wherein the cationic polynuclear metal complex comprises a polynuclear metal complex represented by the following formula (11): [M 11 6 M 12 h (X 11 ) ma (X 12 ) 3ma ] na (11) (In the formula, M 11 represent, independently of each other, an ion of a metal A selected from Group 11 of the Periodic Table, M 12 each independently represents a transition metal B other than the metal A; X 11 indicate, independently of each other, tripodal phosphines X 12 each independently represents an amino acid having a thiol group, h represents 3 or 6 ma represents 1 or 2; na represents an integer from 1 to 12.

23. The ionic solid according to any one of claims 19 to 22, wherein the crystal lattice is formed by one represented by the following formula (12): [{M 11 6 M 12 h (X 11 ) ma (X 12 ) 3ma } na (M 12 p M 13 q )](E) r (12) (In the formula, M 11 represent, independently of each other, an ion of a metal A selected from Group 11 of the Periodic Table, M 12 each independently represents a transition metal B other than the metal A; M 13 each independently represents a metal other than metal A, X 11 indicate, independently of each other, tripodal phosphines X 12 each independently represents an amino acid having a thiol group, h represents 3 or 6 ma represents 1 or 2; n a represents an integer from 1 to 18; E represents an anion or an inorganic acid; p, q, and r each independently represent an integer of 0 or 1 or more, provided that p, q, and r cannot simultaneously be 0.

24. The ionic solid according to any one of claims 21 to 23, wherein the transition metal B is one or more selected from Au, Pd, Ni, Zn, Pt, Cd, Cu and Mn.

25. 25. The ionic solid according to claim 19, comprising a tripodal phosphine and an amino acid having a thiol group as ligands, and the ratio of the tripodal phosphine to the amino acid having a thiol group (tripodal phosphine / amino acid having a thiol group) is 1 / 3 to 1 / 2.

26. 26. An ionic solid according to any one of claims 19 to 25, wherein the tripodal phosphine is 1,1,1-tris(diphenylphosphinomethyl)ethane and the amino acid having a thiol group is penicillamine.

27. The ionic solid according to any one of claims 19 to 26, wherein voids are used as reaction fields.

28. The ionic solid according to any one of claims 19 to 27, wherein the voids are used as reaction fields for a condensation reaction.

29. The ionic solid according to any one of claims 19 to 28, wherein the voids are used as reaction fields for condensation reactions of oxoanions.

30. A method for producing an oxide, comprising using the voids of the ionic solid according to any one of claims 19 to 29 as a reaction field for an oxidation reaction.

Citation Information

Patent Citations

  • Novel dielectric material

    WO2018056237A1

  • Ionic solid

    WO2018079831A1